The Effectiveness of Online Learning Assisted by Edmodo Application on Mastery of Science Concepts and Digital Literacy for Elementary Students - Gumilar, Dani Fajar; Suhandi, Andi (International Conference on Elementary Education, 2021)
The world is currently faced with a covid-19 pandemic situation that affects the entire order of life. In the field of education, it requires alternative learning that can be implemented at home, through distance learning, or online learning. Edmodo is an alternative that can facilitate the learning process online. This study aims to determine the effectiveness of online learning assisted by Edmodo on the mastery of science concepts and the digital literacy of elementary students. The method used in this research is pre-experimental with One Group Pre-test & Post-test design. The research subjects were students of class V SDN Jelegong 02 with a non-probability sample sampling technique from a purposive sample type. The research instrument used was a test of mastery of science concepts and a digital literacy questionnaire. The data analysis technique is by calculating the N-Gain score of each student and then categorizing it into high, medium, and low criteria and determining the effectiveness of learning based on the percentage of students who met the high criteria according to predetermined standards. The results showed that online learning assisted by the Edmodo application was effective for mastery of science concepts with low effectiveness criteria. The results of research on students' digital literacy in terms of individual competence, technical skill aspects, are at the advanced level with moderate effectiveness criteria. In the aspect of critical understanding, it is at an advanced level with moderate effectiveness criteria. Meanwhile, the communicative abilities aspect was at the medium level with low effectiveness criteria.